Physical education with the TPSR model: Building characters and basic manipulative movements in elementary school students - Raharjo, Hermawan Pamot; Kusuma, Donny Wira Yudha; Putra, Ranu Baskora Aji; Irsyada, Roas (UIR Press, 2023)
Character education is an essential aspect of education that transcends academic development. However, its implementation is frequently hindered by students' lack of social responsibility and mutual respect. Through the development of a physical education learning model based on the Teaching Personal and Social Responsibility (TPSR) approach, this study sought to address the fundamental problems inherent in the implementation of character education in schools. Using an experimental method and a pretest-posttest design with 56 elementary school students, this study employed the game Engklek to promote character development and enhance fundamental manipulative skills. The results demonstrated a positive impact on the character traits, knowledge, and abilities of the students, with increased scores at levels 1 and 2. However, there were identified limitations, such as the need for adequate facilities and the limited habituation of character characteristics in daily life due to time constraints. Overall, this research contributes to the development of a physical education learning model that enhances the character development and fundamental manipulative movements of elementary school students, whereas future research should explore alternative materials and interactive learning media to further improve physical education.